Problems of increasing professional competence of library managers - J. B. Avrajeva (Библиосфера, 2013)
They problems of renovating the structure of management personnel, their knowledge, skills, shaping professional elite in provincial libraries of levels are considered. Stress is maid on leaders and specialists knowledge in the field of right, psychologies and others. Special attention is paid to key educational competencies, playing important role in development of a personality.